A Review on Medicinal Fruit Bhokar of Species Cordia dichotoma Forst - A, Dighe Priyanka (International Journal of Pharmaceutical & Biological Archive, 2014)
A Review on Medicinal Fruit Bhokar of Species Cordia dichotoma Forst